Co-Existence of Certain ESBLs, MBLs and Plasmid Mediated Quinolone Resistance Genes among MDR E. coli Isolated from Different Clinical Specimens in Egypt - Salwa Mahmoud Masoud; Rehab Mahmoud Abd El-Baky; Sherine A. Aly; Reham Ali Ibrahem (MDPI AG, 2021)
The emergence of multi-drug resistant (MDR) strains and even pan drug resistant (PDR) strains is alarming. In this study, we studied the resistance pattern of E. coli pathogens recovered from patients with different infections in different hospitals in Minia, Egypt and the co-existence of different resistance determinants. E. coli was the most prevalent among patients suffering from urinary tract infections (62%), while they were the least isolated from eye infections (10%). High prevalence of MDR isolates was found (73%) associated with high ESBLs and MBLs production (89.4% and 64.8%, respectively). blaTEM (80%) and blaNDM (43%) were the most frequent ESBL and MBL, respectively. None of the isolates harbored blaKPC and blaOXA-48 carbapenemase like genes. Also, the fluoroquinolone modifying enzyme gene aac-(6')-Ib-cr was detected in 25.2% of the isolates. More than one gene was found in 81% of the isolates. Azithromycin was one of the most effective antibiotics against MDR E. coli pathogens. The high MAR index of the isolates and the high prevalence of resistance genes, indicates an important public health concern and high-risk communities where antibiotics are abused.